Straight from the cow's mouth: investigating procurement and management strategies in cattle supplied to Great Zimbabwe using a multi-isotopic approach - House, Michell (Department of Archaeology, 2021)
Great Zimbabwe was the centre of an ancient Shona state from AD1200- 1700. It is known for its magnificent architecture and involvement in long-distance (intercontinental) and local (inter-regional) trade. In this society, cattle were vitally important in social, economic and political spheres. However, the origins and herd management strategies of cattle from Great Zimbabwe have never been explored using empirical evidence, although researchers have proposed seasonal transhumance between upland and lowland regions. In this thesis, measurements of 87Sr/86Sr, δ 18O, δ13C and δ15N profiles in serial samples of tooth enamel and dentine from 27 archaeological cattle teeth enable investigation of several aspects of cattle procurement and management. Taken together, the isotope measurements show that cattle at Great Zimbabwe came from a broad geographical area. Some cattle were raised (for the first year of life) less than 40kms away from Great Zimbabwe, most were raised in the lowveld of the country between 40 and 120kms south of the site and some may have moved between the two areas. Cattle fed mainly on C4 grass throughout the period from AD1300 to 1600, although some also consumed limited amounts of browse. Heterogenous δ 13C profiles indicate that animals derived from different environments, and that calves were born at different times of year. This study emphasises the advantages of using multiple isotopes to extract maximum information from archaeological tissues. In combination with the distribution of material culture, particularly from sites coeval with Great Zimbabwe, this study contributes to our understanding of the flow of key resources within the Zimbabwe state, enhancing knowledge of relationships between sites and regions. This study emphasises how economically connected the landscape was during the thriving of the Zimbabwe state. It makes a significant contribution to our hitherto very limited knowledge of the flow of regional (as opposed to imported) commodities. Future work should target lesser studied Zimbabwe-type sites in southern Zimbabwe to further explore interactions and relationships between hinterland sites and their centres.